Poly (Lactic Acid)Nanofibres as Drug Delivery Systems: Opportunities and Challenges - Farnaz Fattahi; Akbar Khoddami; Ozan Avinc (Nanomedicine Research Journal, 2019)
Numerous Scientists have discovered the procedure of nanotechnology, explicitlynanofibers, asdrug delivery systems for transdermal uses. Nanofibers canbe used to deliver drugs and are capable of controlled release for a continued periodof time. Poly (Lactic Acid) (PLA) is the lastly interesting employed synthetic polymer in biomedical application owing to its well categorized biodegradable properties. PLA(−[CH(CH3)COO]n–)is linear biodegradable aliphatic polyester which can be derived from 100% renewable bioresources like rice and wheatthrough fermentation and polymerization. PLA has been accepted by FDA to be applied in biomaterials, such as sutures, bone plates, abdominal mesh, and drug delivery systems. PLA holds stereoisomers,for instancePoly(L-Lactide)(PLLA), Poly(D-Lactide) (PDLA), and Poly(DL-Lactide) (PDLLA). PLGA is a copolymer of PLA and Poly(Glycolic Acid) (PGA) that are most usually used biodegradable synthetic polymers for biomedical applications such as scaffolds and drug delivery systems The objective of this review paper is to highpoint the possibility of PLA nanofibres as drug deliverysubstances and to give full information about the newprogresses about the PLA , PLLA and PLGA nanofibers fabrication as noveldrug delivery systems.